Treatment of depression in the elderly with repetitive transcranial magnetic stimulation using theta-burst stimulation: Study protocol for a randomized, double-blind, controlled trial - Valiengo, Leandro; Pinto, Bianca S.; Marinho, Kalian A. P.; Santos, Leonardo A.; Tort, Luara C.; Benatti, Rafael G.; Teixeira, Bruna B.; Miranda, Cristiane S.; Cardeal, Henriette B.; Suen, Paulo J. C.; Loureiro, Julia C.; Vaughan, Renata A. R.; et al. (Frontiers in Human Neuroscience, 2022)
Introduction: Transcranial magnetic stimulation (TMS) is a consolidated procedure for the treatment of depression, with several meta-analyses demonstrating its efficacy. Theta-burst stimulation (TBS) is a modification of TMS with similar efficacy and shorter session duration. The geriatric population has many comorbidities and a high prevalence of depression, but few clinical trials are conducted specifically for this age group. TBS could be an option in this population, offering the advantages of few side effects and no pharmacological interactions. Therefore, our aim is to investigate the efficacy of TBS in geriatric depression. Methods and analysis: The proposed study is ongoing and designed as a double-blind clinical trial in 108 individuals. Patients will be randomized to TBS or sham treatment. Inclusion criteria include a diagnosis of major depressive episode and a minimum age of 60 years. The coil will be positioned in the dorsolateral prefrontal cortex, with intermittent TBS mode on the left and continuous TBS on the right. There will be 20 consecutive sessions. Outcome measures will be determined before the intervention (baseline) and 1, 2, 4, 6, 8, and 12 weeks after onset of treatment. The main clinical result will be measured using the Hamilton Depression Scale (HDRS) by comparing the initial scores with those obtained at 6 weeks after the intervention. We will use other clinical scales and biomarkers as secondary outcomes and the incidence of adverse events to determine tolerability and safety. Ethics and dissemination: The study was approved by the local Ethical Committee and is expected to be presented in congresses of the area and published in indexed journals. Trial registration: NCT0484292 at https://clinicaltrials.gov/ct2/show/NCT04842929 KEYWORDS: depression; major depressive disorder; elderly; antidepressant; Repetitive transcranial magnetic stimulation (rTMS), theta-burst (TBS).